Melinis maroccana (Melinidinae, Paniceae, Poaceae), a new combination for the Moroccan flora, and comments on related taxa - Crespo, Manuel B.; Alonso, Mª Ángeles; Martínez-Azorín, Mario (Phytotaxa, 2020)
In the framework of a revision of the Iberian Paniceae Brown (1814: 582) for the Flora iberica project, we came across the aggregate of the “Natal grass”, Melinis repens (Willdenow 1797: 322) Zizka (1988: 55), a group of annual to short-lived perennial grasses being native and widely distributed in Tropical Africa, Arabian Peninsula, India, Cape Verde, and the Canary Islands. Only M. repens s.str. is currently naturalised in the Mediterranean basin, America, Australia, southeastern Asia and the Pacific Islands, where it was mostly introduced for ornamental use, forage or stabilization and cover on disturbed sites, and has become an invasive alien species (Kaufman 2012).